2020
DOI: 10.1097/jnn.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden and Associated Factors Among Informal Caregivers of Stroke Survivors

Abstract: Mild to Moderate Caregiver Burden 30 (34)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 27 publications
4
48
2
1
Order By: Relevance
“…We also found a correlation between caregivers’ burden and depression. This finding is in line with those of previous researchers [ 23 , 26 , 28 , 31 ]. In particular, the severity of the caregivers’ burden correlated positively with the severity of depression, and higher depressive symptoms were related to life changes for the worse (higher burden) [ 34 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We also found a correlation between caregivers’ burden and depression. This finding is in line with those of previous researchers [ 23 , 26 , 28 , 31 ]. In particular, the severity of the caregivers’ burden correlated positively with the severity of depression, and higher depressive symptoms were related to life changes for the worse (higher burden) [ 34 ].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, a stroke survivor's functional disability and the gender of an informal caregiver were associated with informal caregiver burden in the USA [26], though we found no such associations in our study. Pucciarelli et al [27] performed a 12-month longitudinal study in order to detect the changes in caregivers' quality of life, anxiety, depression, and burden, and their predictors.…”
Section: Discussioncontrasting
confidence: 93%
“…Many studies have examined the association between caregivers’ burden with patients’ and caregivers’ characteristics [ 18 , 19 , 20 ]. A systematic review revealed that (i) caregivers’ mental health and (ii) time and effort of caregiving responsibilities were associated with caregivers’ burden [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers of individuals with chronic conditions appear to use the internet for general purposes, to access health-related information and track health-related indicators (eg, weight), support, and services [30,31]. Caring for individuals with a chronic condition is considered a major life stressor that negatively affects the health and well-being of caregivers [39][40][41][42]. However, stroke survivor-informal caregiver dyad interventions have predominately focused on the health and well-being of stroke survivors rather than caring for oneself as a caregiver [40].…”
Section: Comparison With Prior Workmentioning
confidence: 99%